Hospital pharmacy practice and medication errors in Brazil. Issue 3 (11th October 2019) - Rocha, Bruna Gabriela; Pereira, Mariana Linhares; Baldoni, André Oliveira; Rocha, Lorena Ayres; Penm, Jonathan; Moles, Rebekah; Sanches, Cristina
Abstract : Purpose: To analyse conformity with the Basel statements focused on patient safety by Brazilian hospital pharmacies. Methods: A web-based cross-sectional study was performed, with data collected from an electronic survey based on the Basel statements, answered by pharmacists from hospitals in all areas of the country. Results: Pharmacists from 111 hospitals from all areas of Brazil participated. It was found that the Brazilian hospital pharmacist performs several services without meeting the minimum requirements to guarantee patient safety in this environment. Conclusion: Much still needs to be done to meet international standards, from training to supervision of services.